Pengaruh Social Media Marketing Instagram dan E-WOM terhadap Keputusan Pembelian Skincare Wardah di E-Commerce - Anggrainy, Lelly Lathifa Hinifah; Supriyono, Supriyono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In this increasingly competitive beauty industry market, skincare companies must have special marketing strategies that keep up with the times. The basis for conducting this research is to examine how social media marketing Instagram and E-WOM influence consumer purchasing decisions for Wardah skincare in e-commerce. Quantitative research applies non-probability sampling and purposive sampling methods as a way to determine sample coverage in the population. Wardah skincare users domiciled in Surabaya are included in the population in this study. A total of 104 participants were involved in obtaining data that supports this research. After tabulation, an analysis stage was carried out which applied Partial Least Square (PLS). Based on the findings of this research, it is shown that both hypotheses are accepted. The social media marketing Instagram and E-WOM variables are proven to have a positive and significant impact on consumer purchasing decisions for skincare products in e-commerce. Furthermore The conclusion of this research explains that purchasing decisions are increasing along with the better quality of social media marketing instagram and E-WOM implemented by the brand, so these two independent variables are important to maintain and improve.